Composition and trophic structure of zooplankton in a shallow temperate estuary (Mondego estuary, western Portugal) - Morgado, Fernando (2007)
The south arm of Mondego Estuary, western Portugal is characterized by shallow depths and marked longitudinal spatial gradients, namely the tidally induced salinity gradient and an eutrophication gradient. The aims of this work were to study the zooplankton composition and trophic structure of the 335 μm taxocenosis in 2 different locations of the salinity and eutrophication gradients in the south arm. The 2 sampling stations displayed significantly different patterns of temporal variations in environmental variables. The total zooplankton density at each station showed significant spatial and temporal variabilities. However, the number of taxa did not show significant differences among months or between sites. The densities of the most abundant taxa significantly differed between the sampling stations and throughout the study period. The zooplankton assemblages were dominated by omnivores, representing 43.9% of the total zooplankton (with herbivores and carnivores representing 4.4% and 0.5%, respectively). Omnivores were significantly more abundant during autumn, winter, and spring, particularly in Oct., Mar., and May, at station 2, and during Jan., Mar., and Apr., at station 1. Herbivores were significantly more abundant during autumn, late winter, and spring particularly at station 1. Carnivores showed low densities throughout the year, being more abundant in summer and autumn. Despite the detected similarities to other temperate estuaries, the results of this work may indicate environmental stresses in this ecosystem: the spatial structure dominates seasonal patterns; and there are low diversities and high numbers of resident populations. This kind of ecological pattern has been previously reported for other biological communities. The prevailing conditions in Mondego Estuary, namely eutrophication, should result in the development of opportunistic adaptive strategies among invertebrates.